Análise numérica e caracterização hiperelástica de metamateriais mecânicos produzidos com impressão 3D - Thiago Teixeira Nardy Barrioni (2021)
Metamaterials are a class of materials that have special properties not found naturally. These special properties are related to the calculated geometric design so that the structure has a desirable response. 3D printers have enabled the production of metamaterials, becoming gradually an accessible technology for many people. This research can be divided into three different stages. The first one was the mechanical characterization of 3D printing filament based on TPU (polyurethane thermoplastic), an hyperelastic material. Based on tensile and compression tests, the 5th order Mooney-Rivlin models seems to be the best option. The second stage was the investigation of how 3D Fused Filament Fabrication (FFF) printers parameters, e.g., filament deposition orientation, flow rate, speed deposition and extrusion temperature affect the overall final specimens’ mechanical properties and its quality. An increase on extrusion temperature combined with a decrease on speed deposition seems to reduce the layers’ deposition failure. No statistical differences were observed on mechanical properties (stiffness and strength) regardless the filament deposition orientation. The last stage was the numerical simulations of two classes of metamaterials, i.e. auxetics and Kirigami-based. In numerical simulations, the auxetic structures showed Poisson ratio values between 5 and 18% higher than theoretical values. Except for the crosschiral auxetic structure, which showed greater variations between theoretical and simulated and needs further investigation (around 50%). The kirigami structures had elongation values close to those in the literature, but it is likely that in physical tests these structures can reach higher values. Applications such as sound mufflers and running shoes (auxetics) and physical therapy adhesive tapes (kirigami) are some that can be mentioned for these structures.